Museum diplomacy in the digital age - Grincheva, Natalia (Abingdon, Oxon ; New York, NY : Routledge, an imprint of the Taylor & Francis Group, 2021)
"Museum Diplomacy in the Digital Age explores online museums as sites of contemporary cultural diplomacy. Building on scholarship that highlights how museums can constitute and regulate citizens, construct national communities, and project messages across borders, the book explores the political powers of museums in their online spaces. Demonstrating that digital media allow museums to reach far beyond their physical locations, Grincheva investigates whether online audiences are given the tools to co-curate museums and their collections to establish new pathways for international cultural relations, exchange and, potentially, diplomacy. Evaluating the online capacities of museums to exert cultural impacts, the book illuminates how online museum narratives shape audience perceptions redefining their cultural attitudes and identities. Museum Diplomacy in the Digital Age will be of interest to academics and students teaching or taking courses on museums and heritage, communication and media, cultural studies, cultural diplomacy, international relations and digital humanities. It will also be useful to practitioners around the world who want to learn more about the effect digital museum experiences have on international audiences"--
1. Introduction: When museums go global and digital: New pathways of museum diplomacy -- 2. Digital museum diplomacy -- 3. Failures of digital repatriation diplomacy: The Virtual Museum of the Pacific: The Australian Museum -- 4. Digital heritage imperialism: "A History of the World in 100 Objects": The British Museum -- 5. Online power of global brands: YouTube Play project: The Guggenheim Museum -- 6. Conclusion. From failures to successes: From the material past to digital futures.
OCLC-licensed vendor bibliographic record.
Keywords: Museum information networks -- Political aspects; Digital media -- Political aspects; Cultural diplomacy; LANGUAGE ARTS & DISCIPLINES / Library & Information Science; SOCIAL SCIENCE / Archaeology